Resonance as a Constraining Factor in the Glocalization of Religion (Glocalism: Journal of Culture, Politics and Innovation, 2020)
In this paper I approach the phenomenon of resonance in the glocalization of religion from a pragmatist perspective with the aim to contribute to the understanding of these still largely overlooked dynamics. Building on my theory on the global repositioning of religion through insights and suggestions coming from sociology (notably the work of Terence McDonnell and his colleagues) and other disciplines such as anthropology and semiotics, I contend that cultural objects circulating in the global cultural network can become relevant to religious actors and trigger a resonance because they are useful to solve specific religious problems. With reference to the greening of religion in Japan and some aspects of Japanese religions’ activities in South Africa and Cuba, I suggest that the solution to such problems, which starts from the realization of some congruences between global ideas/practices and locally shared religious categories, requires both cognitive work and emotional conditions. Moreover, I illustrate how this process implies changes in the structure of a given religious system, takes different shapes for different religious actors, and intertwines significantly with power issues.
Keywords: glocalization; religion; resonance; problem solving; power relations